The performance effects of corporate venture capital: a meta-analysis - Patrick Haslanger; Erik E. Lehmann; Nikolaus Seitz (The Journal of Technology Transfer, 2022)
The effect of corporate venture capital (CVC) investments is far from being conclusively discussed in literature. Although the expected benefits of CVCs for corporations and start-ups are undisputed, empirical evidence is mixed. We combine and analyze the results of 32 CVC studies, including 105,950 observations: Our results suggest that while CVC investments are positively linked to start-ups' and investors' as well as strategic performance, we find no significant relationship between CVC investments and financial outcomes. The effects are moderated by the timing of the investment, the country and industry-effects. For instance, CVC investments in North America and the ICT sector report significant positive effects, while we find no statistical evidence for the health care sector.
Keywords: G24; L25; L26; M13; 600; Corporate venturing; Innovation; Entrepreneurship; Performance; Corporate venture capital (CVC); Meta-analysis